Whole genome sequencing characteristics of Chlamydia psittaci caprine AMK-16 strain, a promising killed whole cell veterinary vaccine candidate against chlamydia infection. - Valentina A Feodorova; Sergey S Zaitsev; Anna M Lyapina; Natalya V Kichemazova; Yury V Saltykov; Mariya A Khizhnyakova; Vitaliy V Evstifeev; Olga S Larionova (PLoS ONE, 2023)
Chlamydia psittaci is a primary zoonotic pathogen with a broad host range causing severe respiratory and reproductive system infection in animals and humans. To reduce the global burden of C. psittaci-associated diseases on animal welfare and health and to control the pathogen spread in husbandry, effective vaccines based on promising vaccine candidate(s) are required. Recently, the caprine C. psittaci AMK-16 strain (AMK-16) demonstrated a high level of protection (up to 80-100%) in outbred mice and pregnant rabbits immunized with these formaldehyde-inactivated bacteria against experimental chlamydial wild-type infection. This study investigated the molecular characteristics of AMK-16 by whole-genome sequencing followed by molecular typing, phylogenetic analysis and detection of main immunodominant protein(s) eliciting the immune response in mouse model. Similarly to other C. psittaci, AMK-16 harbored an extrachromosomal plasmid. The whole-genome phylogenetic analysis proved that AMK-16 strain belonging to ST28 clustered with only C. psittaci but not with Chlamydia abortus strains. However, AMK-16 possessed the insert which resulted from the recombination event as the additional single chromosome region of a 23,100 bp size with higher homology to C. abortus (98.38-99.94%) rather than to C. psittaci (92.06-92.55%). At least six of 16 CDSs were absent in AMK-16 plasticity zone and 41 CDSs in other loci compared with the reference C. psittaci 6BC strain. Two SNPs identified in the AMK-16 ompA sequence resulted in MOMP polymorphism followed by the formation of a novel genotype/subtype including three other C. psittaci strains else. AMK-16 MOMP provided marked specific cellular and humoral immune response in 100% of mice immunized with the inactivated AMK-16 bacteria. Both DnaK and GrpE encoded by the recombination region genes were less immunoreactive, inducing only a negligible T-cell murine immune response, while homologous antibodies could be detected in 50% and 30% of immunized mice, respectively. Thus, AMK-16 could be a promising vaccine candidate for the development of a killed whole cell vaccine against chlamydiosis in livestock.